Implementation of Sleep Hygiene to Improve Sleep Quality among Adolescents at the Maccini Public Health Center - Nurhayati, Nurhayati; Ramdani, Nadia Rahma; Kasim, Erna; Nurbaeti, Nurbaeti (Genius Journal, 2024)
Introduction: Sleep is a natural necessity for all living creatures, including humans, to restore both body and mind. It is a physiological state marked by reduced consciousness, muscle activity, and responsiveness to the external environment. Objective: To evaluate the sleep quality  improvement among adolescents experiencing sleep disorders. Method: This study used a descriptive case study approach with adolescents who reported sleep disorders. Inclusion criteria included adolescents who were willing to participate, while exclusion criteria excluded those with insomnia. Results: The implementation of sleep hygiene over four consecutive days for two respondents resulted in an improvement in sleep quality. Conclusion: Sleep hygiene is effective in improving sleep quality in adolescents.